2021
DOI: 10.1002/admt.202100096
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer Cooperation for Sustainable High‐Performance Oxidase‐Based Biosensing with the Simplest Possible Readout of Substrate Conversion

Abstract: For sustainable high‐quality biosensor preparation, the biopolymers zein and gelatin are placed on Pt electrodes as base‐ and top‐coats, respectively, through simple drop‐and‐dry addition. The gelatin top‐coat of the biocompatible sandwich supports covalent external attachment of glucose oxidase (GOx), ensuring easy access of substrate to enzyme, while the lower, selectively permeable zein base‐coat protects electro‐oxidative detection of enzymically‐produced hydrogen peroxide from interferents. The functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Data acquisition was controlled by the Palmsense-4 software PSTrac5.8 , and individual measurements detected the glucose response of the PAA/GO x -CNT/Pt biosensors as anodic hydrogen peroxide (H 2 O 2 ) oxidation currents through an adjustment of the WE potential to +0.6 V versus RE, this potential being chosen from experience gained in previous glucose biosensing studies. 36 40 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data acquisition was controlled by the Palmsense-4 software PSTrac5.8 , and individual measurements detected the glucose response of the PAA/GO x -CNT/Pt biosensors as anodic hydrogen peroxide (H 2 O 2 ) oxidation currents through an adjustment of the WE potential to +0.6 V versus RE, this potential being chosen from experience gained in previous glucose biosensing studies. 36 40 …”
Section: Methodsmentioning
confidence: 99%
“…A fritted Ag/AgCl/3 M KCl assembly and a Pt wire served as reference electrode (RE) and counter electrode (CE), while the working electrode (WE) was the enzyme-modified Pt disk electrode of standard or SPE design. Data acquisition was controlled by the Palmsense-4 software PSTrac5.8 , and individual measurements detected the glucose response of the PAA/GO x -CNT/Pt biosensors as anodic hydrogen peroxide (H 2 O 2 ) oxidation currents through an adjustment of the WE potential to +0.6 V versus RE, this potential being chosen from experience gained in previous glucose biosensing studies. …”
Section: Methodsmentioning
confidence: 99%
“…By using the method of crosslinked gelatin immobilization, many enzyme-based biosensors were developed for medical diagnosis, such as Pt/zein/gelatin-GOx biosensors ( Figure 1 a) [ 33 ], three-electrode array biosensors ( Figure 1 b) [ 34 ], Pt-PANI@Fe 2 O 3 -GA biosensors ( Figure 1 c) [ 35 ], gelatin/GOx-Pt glucose biosensors ( Figure 1 d) [ 36 ], and AsOx/GB-ZnO/ITO ascorbic acid biosensors ( Figure 1 e) [ 37 ].…”
Section: Gelatin As a Matrix For Immobilized Biorecognition Materialsmentioning
confidence: 99%
“… Biosensors for medical diagnosis with gelatin matrix. ( a ) Pt/zein/gelatin-GOx biosensors-design and fabrication [ 33 ] (copyright (2021) Wiley-VCH GmbH); ( b ) a reusable DIY three-electrode base plate for microfluidic electroanalysis and biosensing [ 34 ] (copyright (2021) American Chemical Society); ( c ) schematic of the biosensor elaboration using PANI@Fe 2 O 3 [ 35 ] (Copyright (2018) by the authors); ( d ) the gelatin/GOx-Pt glucose biosensor fabrication procedure and possible gelatin–GOx conjugations during biocatalyst immobilization [ 33 ] (copyright (2020) The Royal Society of Chemistry 2020); ( e ) proposed electrochemical reaction and synthesis of AsOx/GB-ZnO/ITO bioelectrode [ 37 ] (copyright (2015) Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim). …”
Section: Figurementioning
confidence: 99%
“…Our previous work showed that a gelatin top/zein bottom sandwich on a glucose oxidase biosensor hindered the diffusion of organic acids, drugs, and neurochemicals to the covered electrode. 20 As with the blockage of an inward movement of molecules to the electrode, it was expected that the biopolymer coating would stop outward PB diffusion and consequent loss of H 2 O 2 reduction. To prove the protection from PB leakage and the maintenance of a stable H 2 O 2 response, gelatin-zein-PB/CNT-SPCEs were tested in pH 7.0 Na phosphate buffer at a potential of −150 mV vs RE, with serial additions of 50 μM S8A shows the original set of amperograms from four trials with the same gelatin-zein-PB/CNT-SPCE while Figure 3B displays the plots of the step current in the individual amperometric recordings versus adjusted H 2 O 2 levels.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%